SREBP transcription factors: master regulators of lipid homeostasis - Eberlé, Delphine; Hegarty, Bronwyn; Bossard, Pascale; Ferré, Pascal; Foufelle, Fabienne (Biochimie, 2004)
Sterol regulatory element binding proteins (SREBPs) are a family of transcription factors that regulate lipid homeostasis by controlling the expression of a range of enzymes required for endogenous cholesterol, fatty acid (FA), triacylglycerol and phospholipid synthesis. The three SREBP isoforms, SREBP-1a, SREBP-1c and SREBP-2, have different roles in lipid synthesis. In vivo studies using transgenic and knockout mice suggest that SREBP-1c is involved in FA synthesis and insulin induced glucose metabolism (particularly in lipogenesis), whereas SREBP-2 is relatively specific to cholesterol synthesis. The SREBP-1a isoform seems to be implicated in both pathways. SREBP transcription factors are synthetized as inactive precursors bound to the endoplasmic reticulum (ER) membranes. Upon activation, the precursor undergoes a sequential two-step cleavage process to release the NH 2-terminal active domain in the nucleus (designated nSREBPs). SREBP processing is mainly controlled by cellular sterol content. When sterol levels decrease, the precursor is cleaved to activate cholesterogenic genes and maintain cholesterol homeostasis. This sterol-sensitive process appears to be a major point of regulation for the SREBP-1a and SREBP-2 isoforms but not for SREBP-1c. Moreover, the SREBP-1c isoform seems to be mainly regulated at the transcriptional level by insulin. The unique regulation and activation properties of each SREBP isoform facilitate the co-ordinate regulation of lipid metabolism; however, further studies are needed to understand the detailed regulation pathways that specifically regulate each SREBP isoform.